Sexually Compulsive Behaviors: Implications for Attachment, Early Life Stressors, and Religiosity. - Timberlake, Darla; Meyer, Dixie; Hitchings, Sarah; Oakley, Ashley; Stoltzfus, Lauri; Aguirre, Sharon; Plumb, Amanda (Sexual Addiction & Compulsivity)
The prevalence and rampant growth of sexually compulsive behaviors is recognized as a significant social problem affecting those who struggle with the behaviors, their romantic partners, their families, and other individuals in their social network. The current study investigated the role of attachment, early life stressors (ELS), age, and behavioral religiosity in sexually compulsive behaviors. Results suggested attachment anxiety, ELS, and behavioral religiosity were positively associated with sexually compulsive behaviors while age was negatively associated with sexually compulsive behaviors. Those participants high in sexually compulsive behaviors reported more attachment insecurity and ELS.